O atendimento de bebês em turma do maternal na escola municipal de educação infantil Nair Lima, município de Abaetetuba-PA - PINHEIRO, Dilma Ferreira (2023)
This Course Completion Paper aims to reflect on the teaching of infants in kindergarten classes, especially dealing with early childhood education in the Municipal School of Early Childhood Education Nair Lima (EMEI), municipality of Abaetetuba-PA. The methodology covered qualitative research, with the use of theoretical references such as Didonet (2001), Barbosa (2010), Borba (2007) among others, as well as observations and the application of a questionnaire to two teachers who work at this level of education with kindergarten classes. As a result, although incipient, it is possible to say that Early Childhood Education is important for the comprehensive development of these subjects as well as the educational process faces challenges that need to be faced by those involved in order to ensure the social quality of education.